Training school principals as talent developers : an international perspective - Hayes, Sonya D.; Abdelrahman, Nahed; Irby, Beverly J.; Nafukho, Frederick M. (International higher education (Series), 2022)
Training School Principals as Talent Developers: An International Perspective focuses on how to prepare school principals to lead their schools by training and supporting teachers in their craft. The main goal of schools is improving teaching and learning in order to maximize students' potential to be college ready and career ready. Principals play significant role in improving the instructions which improves students' learning. In order to do so, we need inspiring principals to be talent developers. The book is comprised of chapters written by faculty and researchers from various countries and offers multiple perspectives on training and developing principals to be talent developers.In the ten chapters of this edited book, we wanted to address the perspectives of "who is the role model of a principal, what are the qualities needed to make a good principal and what are the challenges that the talent developer principals encounter to achieve their goals. We also wanted to broaden the lens by addressing these perspectives in the United States and globally.